2023
DOI: 10.1108/ijshe-02-2022-0053
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of environmental knowledge sharing behaviour among accounting educators: a modified theory of planned behaviour

Abstract: Purpose This study aims to explore the determinants of environmental knowledge sharing behaviour among accounting educators through the lens of an extended theory of planned behaviour (TPB). Design/methodology/approach A total of 95 accounting educators responded to a questionnaire survey. The data comprising information on attitude, subjective norm, perceived behavioural control, possession of environmental knowledge and locus of control, as exogenous latent variables and intention to share and environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(189 reference statements)
1
4
0
Order By: Relevance
“…Conversely, if there is no perceived social pressure or norm to watch a particular video, an individual may be less likely to watch it. This finding also matched the results obtained by previous studies that also found the significance of subjective norms in determining people's intention and actual behavior (Nguyen et al, 2023;Abd-Mutalib et al, 2023;Shou et al, 2022;Balikcioglu et al, 2022;Nair, 2021;Ashraf et al, 2019;Wong et al, 2020;Agbetunde et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, if there is no perceived social pressure or norm to watch a particular video, an individual may be less likely to watch it. This finding also matched the results obtained by previous studies that also found the significance of subjective norms in determining people's intention and actual behavior (Nguyen et al, 2023;Abd-Mutalib et al, 2023;Shou et al, 2022;Balikcioglu et al, 2022;Nair, 2021;Ashraf et al, 2019;Wong et al, 2020;Agbetunde et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The results of his research show that critical thinking skills as a predictor have a positive impact on environmental awareness. Meanwhile, Abd-Mutalib (2023) shows that awareness of sharing in collaboration skills can foster concern for the surrounding environment. Orhan (2022) and Abd-Mutalib (2023) are consistent with research on project-based scientific learning, which suggests that environmental awareness can be fostered through critical thinking skills and shared awareness of cooperation skills.…”
Section: Resultsmentioning
confidence: 99%
“…Measuring collaboration skills should have clear objectives. This will positively impact learning outcomes (Harding et al, 2017;Abd-Mutalib et al, 2023). Increasing collaboration skills can foster a caring attitude through sharing knowledge (Wang & Liu, 2020;Jung et al, 2021), sharing solutions to problems (Kwon et al, 2019), and a willingness to interact in the surrounding environment (Ghavifekr, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was corroborated by several prior investigations. According to Abd-Mutalib et al, (2023), injunctive laws increased workers' energy-saving goals at work. In view of Wang et al, (2019), a strong positive association between employees' personal, subjective, and descriptive norms and electricity conservation.…”
Section: Discussionmentioning
confidence: 99%